Antifungal effects of andrographolide and its combination with amphotericin B against selected fungal pathogens - Gayus Sale Dafur; Tuan Noorkorina Tuan Kub; Kirnpal Kaur Banga Singh; Azian Harun; Fatmawati Lambuk; Rohimah Mohamud; Ramlah Kadir; Norzila Ismail; Norhayati Yusop (PeerJ)
Despite advancements in antifungal therapies, the development of resistance to conventional drugs has compromised treatment outcomes, creating an urgent need for novel therapeutic approaches. Andrographolide, a key bioactive compound from Andrographis paniculata, has demonstrated broad-spectrum antimicrobial activity. However, its antifungal potential, particularly against clinically relevant fungi, remains underexplored. Amphotericin B, a classic antifungal drug, is widely used for severe fungal infections, but limited by its toxicity at higher doses. Combination therapy has emerged as a promising approach to improve treatment outcomes, reduce toxicity, and limit the emergence of resistance. The purpose of this study was to evaluate the antifungal efficacy of andrographolide, and in combination with amphotericin B against Candida albicans, Microsporum gypseum, Aspergillus fumigatus, Aspergillus terreus, Aspergillus niger, and Trichophyton mentagrophytes. Antifungal activity was evaluated using broth microdilution susceptibility testing, while combination effects were analyzed using a checkerboard technique, utilizing the fractional inhibitory concentration (FIC) index to assess interaction outcomes. The concentration at which inhibition is minimal (MIC) against the examined isolates ranged between 400 and 800 µg/mL. A. fumigatus, A. niger, and T. mentagrophytes showed higher susceptibility with lower MICs (400 µg/mL), while A. terreus, M. gypseum, and C. albicans required higher concentrations (800 µg/mL) for inhibition. The minimum fungicidal concentration (MFC) values varied, with A. fumigatus and A. niger having MFCs of 800 µg/mL, while the remaining species had MFCs ≥ 1,600 µg/mL. The MFC/MIC ratios indicated fungicidal activity for most isolates, except for M. gypseum and C. albicans. Combination of andrographolide and amphotericin B exhibited antifungal efficacy against A. fumigatus, A. niger, T. mentagrophytes, and C. albicans with FICI values varying from 0.375 to 0.5 (FICI ≤ 0.5) demonstrating a synergistic effect, while it exhibited an additive impact with FICI values of 0.75 (0.5 > FICI ≤ 1.0) against A. terreus and M. gypseum. Andrographolide demonstrated notable antifungal activity, and its combination with amphotericin B enhanced efficacy against certain pathogens. These results highlight andrographolide’s potential as complementary antifungal substance in combination therapies to overcome resistance and reduce toxicity associated with traditional antifungal drugs. However, the variability in response among different fungal species warrants further research to optimize the combination’s clinical application and safety.